Mechanical Thrombectomy With and Without Intravenous Tissue Plasminogen Activator for Acute Ischemic Stroke: A Systematic Review and Meta-Analysis Using Nested Knowledge - Adusumilli, Gautam; Pederson, John M.; Hardy, Nicole; Kallmes, Kevin M.; Hutchison, Kristen; Kobeissi, Hassan; Heiferman, Daniel M.; Heit, Jeremy J. (Frontiers in Neurology, 2021)
Background: Mechanical thrombectomy (MT) is now the standard-of-care treatment for acute ischemic stroke (AIS) of the anterior circulation and may be performed irrespective of intravenous tissue plasminogen activator (IV-tPA) eligibility prior to the procedure. This study aims to understand better if tPA leads to higher rates of reperfusion and improves functional outcomes in AIS patients after MT and to simultaneously evaluate the functionality and efficiency of a novel semi-automated systematic review platform. Methods: The Nested Knowledge AutoLit semi-automated systematic review platform was utilized to identify randomized control trials published between 2010 and 2021 reporting the use of mechanical thrombectomy and IV-tPA (MT+tPA) vs. MT alone for AIS treatment. The primary outcome was the rate of successful recanalization, defined as thrombolysis in cerebral infarction (TICI) scores ≥2b. Secondary outcomes included 90-day modified Rankin Scale (mRS) 0–2, 90-day mortality, distal embolization to new territory, and symptomatic intracranial hemorrhage (sICH). A separate random effects model was fit for each outcome measure. Results: We subjectively found Nested Knowledge to be highly streamlined and effective at sourcing the correct literature. Four studies with 1,633 patients, 816 in the MT+tPA arm and 817 in the MT arm, were included in the meta-analysis. In each study, patient populations consisted of only tPA-eligible patients and all imaging and clinical outcomes were adjudicated by an independent and blinded core laboratory. Compared to MT alone, patients treated with MT+tPA had higher odds of eTICI ≥2b (OR = 1.34 [95% CI: 1.10; 1.63]). However, there were no statistically significant differences in the rates of 90-day mRS 0-2 (OR = 0.98 [95% CI: 0.77; 1.24]), 90-day mortality (OR = 0.94 [95% CI: 0.67; 1.32]), distal emboli (OR = 0.94 [95% CI: 0.25; 3.60]), or sICH (OR = 1.17 [95% CI: 0.80; 1.72]). Conclusions: Administering tPA prior to MT may improve the rates of recanalization compared to MT alone in tPA-eligible patients being treated for AIS, but a corresponding improvement in functional and safety outcomes was not present in this review. Further studies looking at the role of tPA before mechanical thrombectomy in different cohorts of patients could better clarify the role of tPA in the treatment protocol for AIS.